Sustainable Development of Intellectual Property Legislation as a Component of National Security - Yuliia Leheza; Oleh Tsyhanov; Vira Halunko; Andriy Boyko; Volodymyr Buha (Nusantara: Journal of Law Studies, 2026)
The article examines the role of legislation in intellectual property as an important element in ensuring the state’s national security. Analysis of the current state of intellectual property legislation indicates its gradual alignment with international standards, driven by European integration and the development of the innovative economy. At the same time, despite positive trends, several significant problems remain, including ineffective law enforcement, gaps in legal regulation, especially in the context of digitalisation, and a high level of intellectual property rights violations. This situation indicates the need to improve legislation further, taking into account modern challenges and threats. The study’s practical aspect confirms that violations of intellectual property rights can directly affect the state’s national security. In particular, the use of unlicensed software in state bodies or enterprises of strategic importance creates a risk of confidential information leakage and increases vulnerability to cyber threats. In addition, illegal copying or transfer of technologies, including in the military sphere, can lead to the loss of technological advantage and weakening of the state’s defense capabilities. The main threats associated with insufficient legal protection of intellectual property are identified, along with directions for improving legislative regulation in this area. The need for harmonisation of national legislation with international standards is substantiated (WIPO Treaties, WIPO Copyright Treaty (WCT), WIPO Performances and Phonograms Treaty (WPPT), Madrid System for the International Registration of Trademarks, Hague System for the International Registration of Industrial Designs, Patent Cooperation Treaty (PCT).